Barbell acceleration analysis on various intensities of weightlifting - Sato, K.; Fleschler, P.; Sands, W. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
The purpose of this study was to examine how various intensity levels influence the peak barbell acceleration in weightlifting. USA weightlifting resident team members (n=9, men:5 & women:4) participated in this study. They performed two repetitions at intensities of 80, 85, and 90% of 1 repetition maximum (total six repetitions). The peak barbell acceleration was measured at the 2nd pull phase of the snatch/clean. A one-way repeated measure ANOVA was used to analyze the effects of the intensity levels (p = .05). The results showed that intensity has a significant effect on the peak barbell acceleration (F(2,16) = 11.49, p < .001). The peak barbell acceleration decreased as the intensity level increased (80%: 19.63±3.04, 85%: 16.78±3.56, 90%: 13.65±3.50). Comparison between elite and beginners or other power-oriented athletes can be considered in future studies.